PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION DENGAN MEDIA KERTAS LIPAT DALAM PENINGKATAN PEMBELAJARAN PECAHAN DI KELAS IV SD NEGERI 1 KUWAYUHAN TAHUN AJARAN 2016/2017 - Elyawati, Elyawati; Wahyudi, Wahyudi; Chamdani, Muh (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Use of Realistic Mathematics Education using Paper Folding as Media in Improving the Lesson of Fraction for Fourth Grade of SD Negeri 1 Kuwayuhan in the Academic Year of 2016/2017. The objectives of this research are to improve the lesson of fraction for fourth grade through realistic mathematics education using paper folding as media. Subjects of this research were 30 fourth grade students of SDN 1 Kuwayuhan in the academic year of 2016/2017. This research is a collaborative classroom action research (CAR) conducted in three cycles. Each cycle consisted of four stages, namely; planning, conducting, observing, and reflecting. Techniques of collecting data were non-test (observation and interview) and test. The results of this research show that the use of realistic mathematics education using paper folding as media can improve the lesson of fraction for fourth grade of SD Negeri 1 kuwayuhan in the academic year of 2016/2017. Keywords: RME, paper folding media, fraction Abstrak: Penerapan Pendekatan Realistic Mathematics Education dengan Media Kertas Lipat dalam Peningkatan Pembelajaran Pecahan Di Kelas IV  SDN 1 Kuwayuhan Tahun Ajaran 2016/2017. Penelitian ini bertujuan untuk meningkatkan pembelajaran pecahan dengan menerapkan pendekatan Realistic Mathematics Education dengan media kertas lipat di kelas IV SD. Penelitian ini adalah penelitian tindakan kelas kolaboratif yang dilaksanakan dalam tiga siklus. Masing-masing siklus mencakup tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik pengumpulan data menggunakan observasi, wawancara, dokumentasi dan tes. Hasil penelitian ini menunjukkan bahwa penerapan pendekatan Realistic Mathematics Education dengan media kertas lipat dapat meningkatkan pembelajaran pecahan di kelas IV SDN 1 Kuwayuhan. Kata Kunci: Realistic Mathematics Education, Kertas Lipat, Pecahan